2016
DOI: 10.1080/1059924x.2016.1180272
|View full text |Cite
|
Sign up to set email alerts
|

North Carolina Latino Farmworkers’ Use of Traditional Healers: A Pilot Study

Abstract: Farmworkers in the United States experience high rates of injury and illness but have limited access to conventional health care. Farmworkers are often from countries that have active traditional healers, so understanding the use of traditional healers among farmworkers is important. This pilot study (1) describes the use of traditional healers among farmworkers and (2) compares the use of traditional healers by farmworkers to other Latino immigrants. Interviews were conducted in 2015 with 100 Mexican farmwork… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
0
15
1
1
Order By: Relevance
“…Care must be taken in generalizing this medical pluralism to all Mexican immigrants in North Carolina because only individuals who received treatment from a sobador in the previous two years were interviewed. However, previous research indicates that 43% of Mexican-born adults living in North Carolina reported having ever been treated by a sobador , with 8% reporting they had been treated within the past year [13]; we can conclude that the use of these traditional healers is common.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Care must be taken in generalizing this medical pluralism to all Mexican immigrants in North Carolina because only individuals who received treatment from a sobador in the previous two years were interviewed. However, previous research indicates that 43% of Mexican-born adults living in North Carolina reported having ever been treated by a sobador , with 8% reporting they had been treated within the past year [13]; we can conclude that the use of these traditional healers is common.…”
Section: Discussionmentioning
confidence: 77%
“…Brock and colleagues [38] noted that some migrant farmworkers sought treatment for musculoskeletal pain from curanderos and sobadores when they returned to their native country, in part due to lack of knowledge about where to find a traditional healer in Georgia. Latino immigrants and migrants in other locations have reported seeking treatment from curanderos and sobadores in their native country, although not necessarily only in their native countries [13, 19]. This study therefore makes an important contribution to our knowledge about sobador use in the United States.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations